2004
DOI: 10.1211/0022357022458
|View full text |Cite
|
Sign up to set email alerts
|

Antihypertensive and anti-arrhythmic effects of an extract of Radix Stephaniae Tetrandrae in the rat

Abstract: In this study, we determined the effects of an extract of Radix Stephaniae Tetrandrae (RST) on arterial blood pressure and heart weight in deoxycorticosterone acetate-salt (DOCA-salt) hypertensive rats. We also determined the effects of the extract on arrhythmia and infarct induced by myocardial ischaemia and reperfusion in anaesthetized rats. We further compared the effects of the extract with those of tetrandrine, which makes up 7% of the extract and is known to act as a calcium-channel antagonist, and verap… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
10
0
2

Year Published

2008
2008
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(13 citation statements)
references
References 25 publications
1
10
0
2
Order By: Relevance
“…Los estudios preclínicos han demostrado esta actividad en los extractos de la hoja de olivo (Olea europaea), en animales de experimentación, tanto por vía oral como intravenosa (10) ; el ajo (Allium sativum) redujo la presión arterial en ratas hipertensas con ligadura de la arterial renal (11) ; las plantas colombianas Croton schiedeanus, Curatella americana y Lupinus amandus mostraron significativa actividad antihipertensiva en ratas espontáneamente hipertensas (12) ; el extracto acuoso-metanólico de las semillas de Carum copticum causó una caída de la presión arterial, dependiente de la dosis en ratas anestesiadas (13) ; el extracto de la raíz de Stephaniae tetrandrae retornó a sus niveles normales la presión arterial sanguínea en ratas hipertensas por acetato de deoxicorticosterona-sal (DOCA-sal) (14) ; la medicina herbal japonesa Tokishakuyaku-san mejoró la hipertensión y el retardo del crecimiento intrauterino en ratas con preeclampsia inducidas por L-NAME (15) .…”
Section: Introductionunclassified
“…Los estudios preclínicos han demostrado esta actividad en los extractos de la hoja de olivo (Olea europaea), en animales de experimentación, tanto por vía oral como intravenosa (10) ; el ajo (Allium sativum) redujo la presión arterial en ratas hipertensas con ligadura de la arterial renal (11) ; las plantas colombianas Croton schiedeanus, Curatella americana y Lupinus amandus mostraron significativa actividad antihipertensiva en ratas espontáneamente hipertensas (12) ; el extracto acuoso-metanólico de las semillas de Carum copticum causó una caída de la presión arterial, dependiente de la dosis en ratas anestesiadas (13) ; el extracto de la raíz de Stephaniae tetrandrae retornó a sus niveles normales la presión arterial sanguínea en ratas hipertensas por acetato de deoxicorticosterona-sal (DOCA-sal) (14) ; la medicina herbal japonesa Tokishakuyaku-san mejoró la hipertensión y el retardo del crecimiento intrauterino en ratas con preeclampsia inducidas por L-NAME (15) .…”
Section: Introductionunclassified
“…TTD is a unique calcium channel blocker with well-documented effects on limiting hypertension and fibrosis in animal models (4,24,25,28,29,(35)(36)(37)39). These studies have not defined an antifibrotic mechanism for the observed effects on the heart, and the role of hemodynamic load as a mediator of the antifibrotic effects has not been compared or addressed.…”
Section: Discussionmentioning
confidence: 99%
“…L'étude des effets pharmacologiques de la même fraction montre que BpF 2 a un potentiel antihypertenseur, comme les extraits de Stephania tetrandra (Yu et al, 2004) (N'Guessan et al, 2004). Ces mêmes études indiquent que BpF 2 , de 1 à 25 mg/kg de P.C., a des effets hypotenseurs dose dépendante chez le lapin, semblables à ceux des extraits de nombreuses plantes médicinales telles que Mareya micrantha (Abo, 1996;Abo et al, 2000), Daucus carota (Gilani et al,2000), Swartzia madagascariencis (Soro et al, 2004), Heliotropium indicum (Traoré et al, 2002) et Gossypium barbadense (Hasrat et al,2004).…”
Section: Discussionunclassified